Surrogate motherhood : conception in the heart / Helena Ragoné - Ragoné, Helena (Routledge, 2019)
Surrogate Motherhood: Conception in the Heart is a compelling account written with analytical clarity and remarkable compassion. Helena Ragon has given long overdue humanity and voice to the actual participants in the surrogate motherhood experience--a heretofore inaccessible population--and the results are fascinating. Anyone interested in fertility, parenting, reproduction, and kinship, or anyone interested in contemporary culture will want to read this book.
Keywords: Surrogate motherhood.; Surrogate mothers -- Attitudes.